User perceived quality model for web-based system assessment - Ahmad Ibrahim, Siti Rohana; Yahaya, Jamaiah; Deraman, Aziz; Hamdan, Abdul Razak; Jusoh, Yusmadi Yah (Indonesian Society for Knowledge and Human Development, 2018)
The critical issue in software quality is to maintain the relevance of the software to the dynamics requirements and expectations. For the last forty years, many software quality models have been developed that focused on the technical and behavioural aspect of the software and little attention towards user perspective of quality. Our previous works in certification exercises have revealed the needs and rational for software certification from user approach. This is aligned with several new developments such as social networking software, various software on the market and development approach as agile methods that leads to user dominance and control over the software. Thus, users are more criticised and demanded in the quality aspects of the software service that accessible to wide range of people from various categories of users. The users of the web-based systems can be defined in several categories with different interests and perspectives but this research only focuses on web users in general. The new structure of quality model is defined. The enhanced quality model and system are valuable to overcome the limitations of previous models and further improve the application in assessment process and software certification.